Hak Karya Cipta Non-Fungible Token (NFT) Dalam Sudut Pandang Hukum Hak Kekayaan Intelektual - Dewi Sulistianingsih; Apriliana Khomsa Kinanti (KRTHA BHAYANGKARA, 2022)
The purpose of this study is to describe and analyze Non Fungitable Token (NFT) copyrighted works within the framework of Intellectual Property Rights. Technological developments in the trade sector make it easier for artists to publish works to be used as works that have a high selling value. Non-Fungible Token (NFT) is one of the media to use and really helps artists to grow. Although this NFT has existed since 2014, there are still many people who do not understand how the NFT system works. This situation can create confusion regarding who is the owner of the copyright and property rights when the work has been transferred or traded many times. This article focuses on non-fungible token copyrighted works from the point of view of intellectual property rights law. The problems in this article are: namely: barriers to legal protection for non-fungible token copyrighted works within the legal framework of intellectual property rights. This study uses a normative legal research method with a literature study which uses a description technique. The collected data will be processed and analyzed. The result of this discussion is that copyright is only given to the creator of the work, while ownership rights can be granted to any party who buys the work. Then the existence of NFT, which still lacks regulation, requires legal protection for its work and here the legal umbrella is intellectual property rights. Every work on NFT will be registered and registered with IPR so that every work is protected by law.